An Extension of the Gomory Mixed-Integer Algorithm to Mixed-Discrete Variables - Dalton, Robert E.; Llewellyn, Robert W. (Management Science, 1966)
The methods of R. E. Gomory for the iterative solution of the mixed-integer linear programming problem are extended directly to the case where some or all of the variables are nonuniformly discrete, i.e., they are restricted to assume values from certain specified sets of unequally-spaced constants. The algorithm presented is shown to converge in a finite number of steps for a discrete-valued objective function.